1962
DOI: 10.1037/h0040042
|View full text |Cite
|
Sign up to set email alerts
|

Semantic satiation and paired-associate learning.

Abstract: ACKNOWLEDGEMENTIn the course of this research work many have helped me, to whom I can only inadequately express my gratitude.To my advisor, Dr. Wallace E. Lambert, whose careful and constant guidance made completion of this thesis possible, my debt is too great ever to be repaid. INTRODUCTIONThe normal human perceives his environment as a stable and meaningful world of objects, persons, and events, whereas for a newborn child, the same environment probably appears as an aggregate of meaningless shapes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

1965
1965
1987
1987

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…In three different studies (Kanungo & Lambert, 1963b;Kanungo and Lambert, 1964;Kanungo, Lambert, & Mauer, 1962), it was observed that prelearning satiation treatment to high meaningful response items resulted not only in a reduction in meaning of the response items as indexed by semantic differential scales but also in a negative transfer effect on subsequent acquisition of paired associates. In other words, when compared with the control group (which got pre-learning satiation treatment of control words that never appeared in subsequent learning) the experimental group (which got pre-learning satiation treatment of response items) showed an impairment in subsequent learning.…”
Section: Proactive Effects Of Satiation Treatmentmentioning
confidence: 96%
See 3 more Smart Citations
“…In three different studies (Kanungo & Lambert, 1963b;Kanungo and Lambert, 1964;Kanungo, Lambert, & Mauer, 1962), it was observed that prelearning satiation treatment to high meaningful response items resulted not only in a reduction in meaning of the response items as indexed by semantic differential scales but also in a negative transfer effect on subsequent acquisition of paired associates. In other words, when compared with the control group (which got pre-learning satiation treatment of control words that never appeared in subsequent learning) the experimental group (which got pre-learning satiation treatment of response items) showed an impairment in subsequent learning.…”
Section: Proactive Effects Of Satiation Treatmentmentioning
confidence: 96%
“…Consistent with a S-R theoretical framework, semantic satiation is viewed (Kanungo, 1962) as a phenomenon in which the response to or meaning of a verbal stimulus is temporarily extinguished by satiation treatment. The continued repetition of a word leads to two correlated consequences.…”
Section: Learning Interpretationmentioning
confidence: 98%
See 2 more Smart Citations
“…The present study is designed to verify Kanungo & Lambert's (1963) contention that satiation treatment to nonsense items do not result in significant semantic change; and to test the predictions of Kanungo, Lambert, & Mauer (1962), that by using low meaningful S-R pairs one can obtain retroactive facilitation and inhibition effects respectively after interpolated satiation treatment to the response and stimulus items.…”
mentioning
confidence: 93%